2022
DOI: 10.3847/1538-4357/ac8e60
|View full text |Cite
|
Sign up to set email alerts
|

Kilonova and Optical Afterglow from Binary Neutron Star Mergers. I. Luminosity Function and Color Evolution

Abstract: In the first work of this series, we adopt a GW170817-like viewing-angle-dependent kilonova model and the standard afterglow model with a light-curve distribution based on the properties of cosmological short gamma-ray burst afterglows to simulate the luminosity functions and color evolution of both kilonovae and optical afterglow emissions from binary neutron star (BNS) mergers. We find that ∼10% of the nearly-on-axis afterglows are brighter than the associated kilonovae at the peak time. These kilonovae woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 173 publications
0
4
0
Order By: Relevance
“…Their associated kilonova signals may be too faint to be directly detected by present survey projects. However, thanks to the beaming effect of relativistic jets, in Paper I of this series (Zhu et al 2022c), we have shown that a large fraction of cosmological afterglows could be much brighter than the associated kilonovae if the jets move toward or close to the line of sight. Bright afterglow emissions would help us detect potential associated kilonova emissions.…”
Section: Introductionmentioning
confidence: 90%
“…Their associated kilonova signals may be too faint to be directly detected by present survey projects. However, thanks to the beaming effect of relativistic jets, in Paper I of this series (Zhu et al 2022c), we have shown that a large fraction of cosmological afterglows could be much brighter than the associated kilonovae if the jets move toward or close to the line of sight. Bright afterglow emissions would help us detect potential associated kilonova emissions.…”
Section: Introductionmentioning
confidence: 90%
“…Yu et al (2021) estimated the multi-messenger detection rate of Binary Neutron Star Mergers is about 300-3500 yr −1 with a GECAM-like detector for γ-ray emissions and an LSST/WFST detector for optical afterglows. Zhu et al (2021) and Zhu et al (2022) showed that the optimal detection rates of the KNdominated and AG-dominated GRB afterglows events are ∼0.2/0.5/0.8/20 yr −1 and ∼500/300/600/3000 yr −1 for ZTF/Mephisto/WFST/LSST, respectively. There are also some studies looking forward to detecting active galactic nucleus (AGN) and researching AGN physics using WFST survey data (X.-F. Hu et al 2023, in preparation,Su et al 2023.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the topics presented here are fields of active research and are evolving at a fast pace, especially in the latest years after GW170817. The upcoming science runs of the ground-based gravitational wave detector network, currently comprising the Laser Interferometer Gravitational-wave Observatory (LIGO, [295]), Advanced Virgo [296] and KAGRA [297], will likely soon yield at least one new binary neutron star and/or black hole-neutron star merger event (e.g., [298][299][300][301][302][303][304][305][306][307]), hopefully with an associated jet: this will provide new unique insights on the structure of short GRB jets, on the properties of off-axis jet emission in general, and on the incidence of jets, which can be used to constrain the progenitor population (e.g., [308]). With new 'golden' events such as GW170817, direct information on the jet structure can be extracted, e.g., through the methodologies discussed at the end of Section 4.2, provided that a detailed, high-cadence, multi-wavelength dataset will be collected.…”
Section: Discussionmentioning
confidence: 99%